Exploring Teachers’ Communication and Engagement with Digital Media in Education - Novita Damayanti; Dedeh Fardiah; Ari Junaedi; Oji Kurniadi (UPT Publikasi Ilmiah UNISBA, 2025)
This study examines teachers' communication and engagement with digital media in education, emphasizing major changes in teaching practices in the digital age. Using a descriptive quantitative method, data were gathered from 62 elementary school teachers who are members of the Integrated Islamic School Network (JSIT) in Majalengka Regency. The findings show that digital media has shifted from a technical tool to a key strategy that helps teachers design, deliver, and enhance learning in adaptive, participatory, and innovative ways. The novelty of this research is in its comprehensive mapping of teachers' interactions with digital media, including material search, content creation, interactive delivery, and its influence on teacher motivation and student engagement. Most teachers reported high emotional and professional engagement when using digital media. However, the adoption of technology in learning evaluation still encounters resistance due to concerns about the validity of instruments, data security, and technical limitations. The implications of this research highlight the need for strategies to enhance teachers' literacy and technopedagogical skills, upgrade digital infrastructure, and establish sustainable institutional support. These findings provide valuable insights for shaping educational policies and promoting innovative learning practices, fostering a more inclusive, effective, and sustainable educational transformation in the digital age.